FATTY ACID METHYL ESTER FROM JATROPHA CURCAS OIL AS A NEW (ECOFRIENDLY) BASED DRILLING FLUID - KANIA, DINA (2012)
The purpose of this study is to investigate the potential use of fatty acid methyl ester (FAME) derived from Jatropha curcas oil as a new eco-friendly base drilling fluid. As concerns over environmental problem caused by mud spills and disposal of using diesel oil based mud, low aromatic synthetic oils has been used as alternatives. However, the environmental legislation and controls still consider the synthetic oils unsuitable due to their non-biodegradability. The sustainability and biodegradability of proposed non-edible vegetable oil Jatropha FAME mud promises a suitable and economical new base fluid. Prior to the drilling fluid formulation, Jatropha curcas oil is processed to FAME by esterification and transesterification. The drilling fluid properties measurements, which consist of electrical stability and rheological properties (plastic viscosity, yield point and gel strengths), are then followed. In order to investigate mud stability under down-hole condition, each sample was mildly agitated by hot rolling for 16 hours at 200 or 250°F before re-measuring the above mud properties.